AN OPTIMAL ALGORITHM FOR SOLVING PROTECTION PROBLEMS IN ELASTIC OPTICAL NETWORKS - Khac An, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
Protection in the network is one of the central problems of optical network design and belongs to the NP-hard problem class. The problem becomes increasingly complicated in the Elastic Optical Network (EON), today’s new optical network. In the EON network, the protection problem must consider additional factors such as energy consumption, frequency distribution requirements, and distribution of modulation formats. Most previous studies focused on proposing approximate solutions to the problem. This paper presents an exact optimization approach using directed p-cycles and a Column Generation algorithm to solve the protection problem efficiently. Our model integrates energy consumption, frequency slot continuity, and modulation constraints. Experiments on NSFNET and USANET show that the proposed method reduces energy consumption by 10–15% and maintains optimality gaps under 10%, outperforming previous models such as EDPC in both efficiency and scalability.